PERAN UNITED NATIONS ENVIRONMENTS PROGRAMME (UNEP) DALAM PENGEMBANGAN EKONOMI HIJAU DI INDONESIA TAHUN 2023-2024. - Asril, Ridho Maulana; Saeri, Mohammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to examine and analyze the role of the United Nations Environment Programme (UNEP) in supporting the implementation of the Just Energy Transition Partnership (JETP) as part of Indonesia's transition towards a green economy during the 2023–2024 period. The research focuses on UNEP's involvement in international cooperation supporting energy sector reform and the integration of just transition principles in Indonesia. This paper employs a descriptive qualitative approach using a literature study method involving the review of books, journals, official reports, scientific articles, and relevant international institution websites. The perspective used is liberalism at the group level of analysis, with cooperation theory serving as the main conceptual framework. The study finds that UNEP acts as an international catalyst in strengthening Indonesia's energy transition strategy through the implementation of the JETP. This role includes providing technical support in policy formulation, facilitating access to international funding, and enhancing national institutional capacity. However, various challenges such as policy overlap, fossil fuel dominance, and limited public participation remain major obstacles. Policy harmonization among institutions, accelerated disbursement of green funding, and enhanced civil society engagement are necessary to ensure the energy transition genuinely supports the achievement of an inclusive and sustainable green economy. Keywords: Green Economy, United Nations Environment Programme (UNEP), Sustainable Development